Development of Tourism in Uzbekistan and Cultural-Historical Tourist Resource Potential of Kashkadarya Region - NAZAROV, Mamatkodir I.; JUMAEV, Hayrulla H.; TURDIMAMBETOV, Izimbet R.; YANCHUK, Sergey L.; EGAMBERDIEVA, Matluba M. (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020, 2020)
Abstract : In the modern world economic development, the tertiary sector plays an important role in the life of different countries. Tourist-reaction services are gaining importance in this regard. The main goal of this study was to analyze the potential of the cultural and historical tourism resource of the Kashkadarya region and to identify its regional features. Conditions of tourism formation in Uzbekistan have been analyzed. Attention was paid to existing recreational potential and the effectiveness of its use. The specificity of the classification of tourism recreational resources based on the research of scientists has been clarified. The potential of the Kashkadarya region tourist recreational resources, which plays a special role by its resource potential in the development of tourism in Uzbekistan, has been analyzed as an example of monuments of material and cultural heritage, at the scale of urban and rural areas. It was found that the Kashkadarya region has immense potential due to cultural heritage and natural recreational potential.